Novo Modelo de Mucosite Intestinal Induzida pela AssociaÃÃo de Irinotecano e 5-Fluorouracil em Camundongos C57BL/6 - VenÃcia Bruna MagalhÃes Pereira (2013)
Introduction: Intestinal mucositis is a common side effect of anticancer regimens for first-line treatment of colorectal cancer. Among such drugs are irinotecan and 5-FU used in combination. Many studies have been conducted on the pathogenesis of MI. However, further investigations are necessary, because the course of MI may vary according to the drug regimen and employees. Then aimed to develop a new experimental model of MI induced by the combination of IRI and 5-FU in mice. Methods and Results: C57BL/6 mice (20-25g, n=6) were injected with saline (100ÂL, i.p), IRI (30 or 45 mg/kg, i.p), 5-FU (25, 37.5 or 50 mg/kg, i.p) or IRI+5-FU for 4 days. On day 7, diarrhea, weight loss, and blood leukocyte count were registered. Following animal euthanasia, ileum samples were collected for histopathological analysis, myeloperoxidase activity (MPO, neutrophil/mg protein), TNF-α and IL-6 levels (pg/mg tissue). Kaplan-Mayer log rank test, Kruskal Wallis/Dunnâs or ANOVA/Bonferroniâs test was used for statistical analysis. p<0.05 was accepted. The best dose combination able to induce IM with no important mortality on day 7 was 5-FU (37.5 mg/kg) +IRI (45 mg/kg) (0% mortality), which was then used for subsequent studies. IRI+5-FU induced (p<0.001) diarrhea (2[0-3]), weight loss (86.7Â3.9g), and leukopenia (7.3Â 2.3 x103) versus saline group (0[0-1]; 101.1Â0.6; 215.5Â 54.1, respectively) or each drug given alone (5-FU: diarrhea (0[0-1]), weight loss [92.6Â2.7], and leukopenia [30.4Â 13.4]; IRI: diarrhea (0[0-1]), weight loss [94.8Â2.1], and leukopenia [49.2Â 5.5]). In addition, IRI+5-FU induced inflammatory cells infiltration, and loss of villi and crypt architecture (4[3-4]), increased in MPO activity (14641Â1598 neutrophil/mgproteÃn), TNF-a (3.2Â0.9 pg/mg tissue), IL-6 (1.4Â0.5 pg/mg tissue) tissue levels versus saline-injected group (0[0-1], 5747Â1155; 0.7Â0.2; 0.3Â0.1) or the drugs injected alone (5-FU: Intestinal damage (2.5[2-3]), MPO [3788Â1212], TNF-α [0.7Â0.2], IL-6 [0.2Â2.3]; IRI: Intestinal damage (1[0-2]), MPO [3580Â1613], TNF-α [0.4Â0,2], IL-6 [0.07Â0.05]) (p<0.05). Conclusion: We developed a new experimental model of IM induced by the combination of IRI+5-FU in mice, which opens perspective for a more appropriate knowledge concerning the pathogenesis of IM.